2019
DOI: 10.1177/1534484319836315
|View full text |Cite
|
Sign up to set email alerts
|

Employee Adaptive Performance and Its Antecedents: Review and Synthesis

Abstract: The purpose of this article is to critically review current studies on employees’ adaptive performance and to integrate the findings to provide insights on how to develop employees’ adaptability. It also aims to identify gaps in the research to guide future studies on adaptive performance in the field of human resource development. By reviewing 34 empirical studies on adaptive performance published between 1999 and 2016, we identified 22 antecedents of adaptive performance at the individual (nine), job (six), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(202 citation statements)
references
References 87 publications
7
146
0
2
Order By: Relevance
“…Among them, the former mainly involves problem-solving skills and flexible use of knowledge; the latter includes mentality adjustments in response to task changes (Allworth and Hesketh, 1999). As mentioned above, the individual's general cognitive ability, self-efficacy, personality traits, and environmental factors in the team have a significant impact on adaptive performance (Tolentino et al, 2014;Park and Park, 2019).…”
Section: Mentoring and Adaptive Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Among them, the former mainly involves problem-solving skills and flexible use of knowledge; the latter includes mentality adjustments in response to task changes (Allworth and Hesketh, 1999). As mentioned above, the individual's general cognitive ability, self-efficacy, personality traits, and environmental factors in the team have a significant impact on adaptive performance (Tolentino et al, 2014;Park and Park, 2019).…”
Section: Mentoring and Adaptive Performancementioning
confidence: 99%
“…Based on COR theory, in a mentorship, protégés obtain knowledge and skills, relational resources, psychological resources, and opinions (Mao et al, 2016) to cope with job changes. In addition, new knowledge, skills, and positive emotions are necessary prerequisites for employees to adopt adaptive behaviors (Park and Park, 2019). It can be observed that mentoring is conducive to thriving at work and that the adaptive performance level is higher.…”
Section: Moderating Role Of Promotion Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now hardly any studies looked at how characteristics of the task or how the change itself influences the (adaptive) performance on the task (see e.g Jundt, Shoss, & Huang, 2015;Park & Park, 2019). Gillie and Broadbent (1989) conducted four experiments on characteristics 38 39 2 2 unforeseen changes in a task or a job, which is clear when looking at the related fields that are described in this review.…”
Section: Task Characteristicsmentioning
confidence: 99%